Spatio-temporally focused femtosecond laser pulses for nonreciprocal writing in optically transparent materials - Vitek, Dawn N. (2010)
Simultaneous spatial and temporal focusing (SSTF) provides precise control of the pulse front tilt necessary to achieve nonreciprocal writing in glass. The magnitude of the pulse front tilt may be adjusted over several orders of magnitude. Nonreciprocal writing was observed for a larger range of focal depths within the sample using SSTF, and nonreciprocal ablation patterns on the surface were revealed. Further, the lower numerical aperture (0.04 NA) utilized with SSTF increases the rate of writing. This technique allows channels in microfluidic devices to be prototyped an order of magnitude faster than with current methods.